The new Mission of Agricultural Research and Extension in West-African Agriculture - Dirk Kohnert; Paul Weber (Sociologia Ruralis - Journal of the European Society for Rural Sociology, 1991)
Recent evaluations of rural development projects in Africa revealed a disappointingly low degree of adoption of the proposed messages or technology packages. This apparent ineffectiveness of the conventional agricultural research and extension system is due to the lack of innovations adapted to specific constraints of the different farming systems of resource-poor farmers, as well as to outmoded concepts of rural development. To overcome this bottleneck the authors propose new roles for agricultural research and extension in Africa: the search for viable innovations should not be left to conventional agricultural research alone. The latter should focus on the development of sustainable strategies, answering those problems (macro-economic, social, ecologic) which would be neglected, if one merely attempted to meet short-term individual interests. Indigenous agricultural systems of knowledge would have to be revitalized as well. One of the main tasks of research and extension services should be to support farmers' experimentation in providing viable options, limiting risk, and analysing and developing indigenous knowledge. The communication of solutions should be left to more efficient external channels, either of the peasantry itself or of professional organizations. – – "La nouvelle mission de recherche et d'extension agricoles dans l'agriculture ouest-africaine": Les récentes évaluations des projets de développement rural en Afrique révèlent que les solutions proposées ou les "paquets technologiques" ne sont que très peu adaptes. Cette apparente inefficacité de la recherche agronomique académique et des systèmes de vulgarisa¬tion est du a I' absence d'innovation adaptée aux contraintes propres des différents systèmes de production des paysanneries pauvres aussi bien qu'aux concepts démodes utilises pour le développement rural. Pour dépasser ce blocage, les auteurs proposent de nouveaux objectifs pour la recherche agricole et la vulgarisation en Afrique. La recherche d'innovation viable ne consisterait pas en la seule recherche agronomique conventionnelle. Cette dernière devrait se focaliser sur le développement de stratégies d'autosubsistance, apportant des réponses a ces problèmes (macro-économiques, sociaux, écologiques) qui seraient négliges, si on ne s'attachait qu'aux intérêts individuels a court terme. Les systèmes agraires indigènes doivent être remis a l'honneur. Une des principales missions des services de recherche et de vulgarisation serait d'apporter leur soutien aux essais mis en place par des agriculteurs pour développer des options viables, limitant le risque, s'appuyant et développant le savoir-faire local. Les résultats devraient être communiques par des canaux extérieurs plus efficaces, aussi bien parmi les paysans eux-mêmes, que parmi les organisations professionnelles.
Additional information: Author's version
Keywords: O2; O55; Q; 300; agricultural extension; West Africa; traing & visit approach (T+V); development policy